Jewellery box: inspired by Istana Budaya / Mohamad Nur Iqbal Mohd Nizam - Mohd Nizam, Mohamad Nur Iqbal (2022)
The Istana Budaya or also known as the palace of culture, is Malaysia's main venue for all types of theatre including musical theatre, operetta, classical concerts and opera from local and international performances, the building also have a unique structure shape. This jewellery box is for filling jewelry. In addition, this jewelry box is inspired from interesting buildings in Malaysia.